INFUSING A GAMIFICATION MECHANISM THROUGH DUOLINGO FOR ENGLISH SPEAKING PROFICIENCY: PERCEPTIONS OF THE INDONESIAN EFL INSTRUCTOR AND STUDENTS - Mahbub, Moh. Arif; Romsi, Abdur; Bulqiyah, Suhaimah; Firdaus, Ifan Andri (Universitas Islam Balitar, 2020)
This current study is to examine both EFL instructor and students concerning the use of Duolingo for English speaking proficiency. To serve this purpose, an explanatory research design was employed. A set of questionnaire and semi-structured interview developed as the primary instruments for this current study. One EFL instructor and ten EFL students in one of the private Islamic Senior High School in Situbondo, Indonesia, involved as research participants in this study. In general, they perceived Duolingo in a positive ways. The findings resulted from semi-structured interview carried out with EFL instructor and the samples of the students revealed that Duolingo facilitated him/her in managing the classwork and assessment. However, some participants also reported several drawbacks. Conclusions, limitations, and recommendations were made for the further research.